2001
DOI: 10.1080/cmt.4.1.42.48
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic breast density during hormone replacement therapy: effects of continuous combination, unopposed transdermal and low-potency estrogen regimens

Abstract: HRT regimens were shown to have different effects on the normal breast. There is an urgent need to clarify the biological nature and significance of a change in mammographic density during treatment and, in particular, its relation to symptoms and breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 25 publications
3
19
0
2
Order By: Relevance
“…Similar to our results, previous studies have shown a strong positive association between EPT use and breast density [13,14,32,33]. Most previous studies have found no association between breast density and ET [13,34].…”
Section: Discussionsupporting
confidence: 94%
“…Similar to our results, previous studies have shown a strong positive association between EPT use and breast density [13,14,32,33]. Most previous studies have found no association between breast density and ET [13,34].…”
Section: Discussionsupporting
confidence: 94%
“…Only the MLO view of the left breast was used for the visual classifications of breast density. Previous studies have shown very little difference between the left and right breast in the response to hormonal treatment 16,19 . For technical reasons, for example, to avoid the pectoral muscle when the assessable area was defined, the CC view was used for the digitized assessment.…”
Section: Mammographic Breast Densitymentioning
confidence: 98%
“…proliferation increases following estrogen/progestogen HT irrespective of the chemical structure of the progestogen. Also mammographic breast density, another important surrogate marker for breast cancer risk, has been shown to increase significantly when NETA, dienogest or medroxyprogesterone acetate was given in addition to estrogen in different studies [18,31,32]. Significant negative correlations were found between fT and mammographic density in women given estradiol in combination both NETA and dienogest [18].…”
Section: Discussionmentioning
confidence: 88%